Coverage quality measuring and optimization for moving target in sensor networks - SHEN Xing-fa1; CHEN Ji-ming2; WANG Zhi2; DAI Guo-jun1 (Tongxin xuebao)
The coverage quality measuring and optimization problems were studied using moving target tracking as the application background. Based on the idea of grid discretization, a graph-theory based algorithm was proposed to search minimal exposure path for the moving target barrier coverage problem using exposure as the performance metric. And a multi-step incremental barrier coverage optimization method was proposed based on the minimal exposure path. The proposed algorithms’ performance was validated by simulation experiments in the end. Experiments show the algorithms are applicable to the barrier coverage problems with arbitrary node distribution model,sensing model,network charac- teristics and moving path of the target, can decrease the number of nodes need to be deployed in order to meet the specific coverage quality requirement and accordingly cut the network cost significantly.